Equity in Student Achievement Across OECD Countries An Investigation of the Role of Policies - Causa, Orsetta (OECD Economics Department Working Papers, 2009)
This paper focuses on inequalities in learning opportunities for individuals coming from different socioeconomic backgrounds as a measure of (in) equality of opportunity in OECD countries and looks at the role played by policies and institutions in shaping countries' relative positions. Based on harmonised 15- year old students' achievement data collected at the individual level, the empirical analysis shows that while Nordic European countries exhibit relatively low levels of inequality, continental Europe is characterised by high levels of inequality - in particular of schooling segregation along socio-economic lines - while Anglo-Saxon countries occupy a somewhat intermediate position. Policies allowing increasing social mix are found to reduce school socio-economic segregation without affecting overall performance. Countries that emphasise childcare and pre-school institutions exhibit lower levels of inequality of opportunity, suggesting the effectiveness of early intervention policies in reducing persistence of education outcomes across generations. There is also a positive association between inequality of opportunities and income inequality. As a consequence, cross-country regressions suggest that redistributive policies can help to reduce inequalities of educational opportunities associated with socioeconomic background and, hence, persistence of education outcomes across generations